LISTENING COMPREHENSION AS A FOREIGN LANGUAGE SKILL - Інна Шимків (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
This article reveals the basic features of listening comprehensive that are very constituent of communicative activity; listening comprehensive is analyzed, and attention is concentrated on the importance of its development in the teaching of future specialists. The nature of listening comprehension as a foreign-language skill is considered. Essential features of neuro-linguistic programming strategies used to teach listening are outlined. The system of teaching listening and its major levels are analyzed within the framework of communicative language teaching. The structural characteristics of listening comprehension on the basis of its psychophysiological mechanisms are elucidated. Listening comprehension difficulties caused by the physical settings are determined. Phonetic, lexical and grammatical problems encountered in listening are identified. It has been proved that both linguistic and non-linguistic types of knowledge, as well as various factors of communicative situation are essential for efficient listening comprehension. The characteristic features of handouts and worksheets used to overcome listening comprehension difficulties are defined. The study concludes with the integral part of listening comprehension in second language instruction and the need to improve the receptive mechanisms ensuring the efficiency of teaching listening.